WRF-LTNGDA: A lightning data assimilation technique implemented in the WRF model for improving precipitation forecasts. (February 2016) - Giannaros, Theodore M.; Kotroni, Vassiliki; Lagouvardos, Konstantinos
Abstract: This study introduces WRF-LTNGDA, a lightning data assimilation technique implemented in the Weather Research and Forecasting (WRF) model. This technique employs lightning for improving the representation of convection by means of controlling the triggering of the model's convection parameterization scheme. The development and implementation of WRF-LTNGDA was carried out in a framework that could easily allow for its exploitation in real-time forecasting activities. The assimilation algorithm was evaluated over eight precipitation events that took place in Greece in the years 2010–2013. Results clearly show that lightning forcing has a positive impact on model performance. The conducted analysis revealed that the employment of WRF-LTNGDA induces statistically significant improvements in precipitation verification scores, especially for high rainfall accumulations. Separate examination of one of the eight case studies highlighted the overall better agreement between the modelled and observed spatial distribution of precipitation when lightning data assimilation was applied, than in the control simulation. Highlights: WRF-LTNGDA: a lightning data assimilation technique for the WRF model. WRF-LTNGDA is evaluated over eight case studies in Greece. Lightning assimilation improves precipitation prediction. WRF-LTNGDA can be used for real-time weather forecasting applications.